Pengaruh Kombinasi Zat Pengatur Tumbuh BAP dan IAA terhadap Pertumbuhan dan Perkembangan Tanaman Daun Dewa (Gynura procumbens (Back)) dalam Kultur in Vitro - Ardianto Mufa'adi; Sandra Arifin Aziz; Diny Dinarti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
Gynura procumbens (Back) has been used for traditional medical treatment in Indonesia. Micropropagation. one of propagation methods, becomes an effective method in propagating the G. p.rocumbens (Back). The in vitro research using The group Randomize Block Design was conducted to study the growth and development of G. procumbens (Back) explant by applying combinations of BAP ( 0, /,2, and 3 ppm) and IAA (0, 0.5, and / ppm) in the Murashige and Skoog (MS) medium. The results showed combination of BAP 3 ppm and IAA 0.5 ppm was the optimum combination for the shoot multiplication, which produced 85.4 shoots per bottle. BAP 3 ppm combined with / ppm of lAA resulted in 100 % callussed culture with the largest diameter. Key words: Gynura u.rocumbens (Back), BAP, IAA, in Vitro